Values of Moderation and Religious Practices in the Pandemic Era: A Philosophical Perspective - Biyanto Biyanto (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2022)
This article discusses moderation and religious practices in the pandemic era. The discussion in this article uses a philosophical perspective. This discussion is vital because the pandemic era has changed people’s religious frame of mind, attitudes, and behaviour. It is not only the religion of Muslims who have changed, but also non-Muslims. Therefore, this article seeks to elaborate on the religious model of the people during the pandemic and the arguments put forward by religious figures who are members of religious organizations. The conclusion from the discussion in this article is that religious moderation in the pandemic era has been reflected in various religious activities, such as worshipping at home, working and studying from home, awareness of taking part in vaccination, mutual social help (al-ta‘āwun), and worshipping virtually. These religious practices refer to the Qur’ān, Hadīth, views of ulama, and scientific and health considerations. In essence, religious people understand that maintaining personal health and safety must be prioritized.",